Pemberdayaan Masyarakat Berbasis Ekowisata Cafe Lembah Pelangi Berbasis Penyuluhan dan Pelatihan Smart Energy Di Blimbingsari, Kabupaten Sleman - Benedictus Mardwianta; Eko Poerwanto; Teguh Wibowo; Abdul Haris Subarjo (ISAS (Indonesian Society of Applied Science), 2025)
The Rainbow Valley Ecotourism Empowerment Program based on Smart Energy in Blimbingsari Hamlet, Caturtunggal, Depok, Sleman aims to enhance community independence through sustainable tourism management integrated with renewable energy technology, particularly solar panels, as well as the development of culinary and handicraft businesses and digital marketing strategies. Key activities include training in solar panel installation and maintenance, community-based tourism destination management, entrepreneurship, digital marketing and basic bookkeeping workshops, and training in making tables and chairs from used barrels as a form of environmentally friendly innovation. The program also emphasizes the importance of collaboration between universities, local government, and the local community to strengthen an independent, creative, and competitive tourism ecosystem. Thus, this program not only contributes to the improvement of the local economy but also supports the achievement of the SDGs for decent work, economic growth, sustainable settlements, and university KPI, namely students' off-campus experiences and the application of lecturers' research results in the community. This community service activity was enthusiastically received and successfully enhanced the participants' knowledge. This is evident from the results of the pretest and posttest